THE INFLUENCE OF TEACHERS' RESPONSES IN THE 4.0 INDUSTRIAL REVOLUTION ON TEACHER PERFORMANCE AT SMPN 1 SOPPENG RIAJA, KIRU-KIRU, BARRU - Erwin Hafid; Baharudin Baharudin; Rahmat Gusnadi; Daniel Rahman (Universitas Islam Negeri Alauddin Makassar, 2022)
This Research aims to find out the Effect of teacher's Responses in the Industrial Revolution 4.0 on Teacher Performances at SMPN 1 Soppeng Riaja Ward Kiru-Kiru Regency Barru. This research used a quantitative method with a population of teachers at SMPN 1 Soppeng Riaja totaling 37. Data collection used observation, questionnaire and documentation. Data analysis used descriptive analysis and inferential analysis used simple regression. The result of descriptive data analysis showed that teacher's responses to industrial revolution 4.0 were in the medium category with 23 respondents with a percentage of 62.2% and teacher performances in the medium category with 21 respondents out of a total of 37 respondents with a percentage of 56.75%. The results of inferential statistical analysis showed the value of = 195.712 > = 2.030. Then, the alternative hypothesis is accepted and is rejected, meaning that there is an effect of the teacher's response to the 4.0 industrial revolution on teacher performance at SMPN 1 Soppeng Riaja , Kiru-Kiru village, Barru district.